Rutile nano-bio-interactions mediate dissimilar intracellular destiny in human skin cells - Sanches, P. L.; Souza, W.; Gemini-Piperni, S.; Rossi, A. L.; Scapin, S.; Midlej, V; Sade, Y.; Paes Leme, A. F.; Benchimol, M.; Rocha, L. A. [UNESP]; Carias, R. B.; Borojevic, R.; et al. (Royal Soc Chemistry, 2019)
The use of nanoparticles (NPs) in the healthcare market is growing exponentially, due to their unique physicochemical properties. Titanium dioxide nanoparticles (TiO2 NPs) are used in the formulation of sunscreens, due to their photoprotective capacity, but interactions of these particles with skin cells on the nanoscale are still unexplored. In the present study we aimed to determine whether the initial nano-biological interactions, namely the formation of a nano-bio-complex (other than the protein corona), can predict rutile internalization and intracellular trafficking in primary human fibroblasts and keratinocytes. Results showed no significant effect of NPs on fibroblast and keratinocyte viability, but cell proliferation was possibly compromised due to nano-bio-interactions. The bio-complex formation is dependent upon the chemistry of the biological media and NPs' physicochemical properties, facilitating NP internalization and triggering autophagy in both cell types. For the first time, we observed that the intracellular traffic of NPs is different when comparing the two skin cell models, and we detected NPs within multivesicular bodies (MVBs) of keratinocytes. These structures grant selected input of molecules involved in the biogenesis of exosomes, responsible for cell communication and, potentially, structural equilibrium in human tissues. Nanoparticle-mediated alterations of exosome quality, quantity and function can be another major source of nanotoxicity.